Influence of β-Glucan Structures and Contents on the Functional Properties of Low-Fat Ice Cream During Storage - Marek Aljewicz; Aleksandra Florczuk; Aneta Dąbrowska (Polish Journal of Food and Nutrition Sciences)
The study aimed to determine the effect of the addition level and structure of β-glucans on the functional properties and sensory attributes of low-fat ice cream. The experimental ice cream was produced with the addition of 0.5% and 1% highly purified (1-3)(1-4) and (1-3) β-glucans. β-Glucans significantly increased overrun and decreased the melting time. The study demonstrated that the β-glucan structure and addition level significantly influenced the consistency and viscosity index, flow behavior, cohesiveness, and firmness of ice cream. The use of (1-3)(1-4) β-glucan led to a significant decrease (~38%), whereas (1-3) β-glucan led to a significant increase (~42%) of ice cream firmness. β-Glucans influenced the sensory properties of ice cream, in particular its texture and mouthfeel. β-Glucans had no significant effect on the taste of ice cream. (1-3)(1-4) β-Glucan isolated from oats is suitable for the production of calorie-reduced ice cream with functional characteristics most similar to the control ice cream (full-fat, with stabilizing substances).